2020
DOI: 10.1016/j.jmapro.2019.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the mechanical load and thermal history during friction stir channelling under constant position and constant force control modes

Abstract: In the present investigation, constant position and constant force process control modes; and representative process temperature measurements were analysed during the application of the friction stir channelling process. The experimental tests were carried out using rolled plates of AA5083-H111 with thickness of 15 mm. Results show that the FSC process was found not stable during the forward traverse movement stage when it is performed via position control. For both control modes, the tool was subjected to a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…When welding is at a constant traverse speed, F x , F y and F z decrease simultaneously with the increase in tool rotational speed (600-800 r/min). It is because increasing the ratio of rotational speed and traverse speed (n/v) indicates the increase in welding heat input and the softening of the material around the tool is intensified during the welding process [22,23]. Moreover, an abnormal F y of 0.5 kN at the welding condition 800 r/min and 150 mm/min is noticed.…”
Section: Welding Force Characteristicsmentioning
confidence: 99%
“…When welding is at a constant traverse speed, F x , F y and F z decrease simultaneously with the increase in tool rotational speed (600-800 r/min). It is because increasing the ratio of rotational speed and traverse speed (n/v) indicates the increase in welding heat input and the softening of the material around the tool is intensified during the welding process [22,23]. Moreover, an abnormal F y of 0.5 kN at the welding condition 800 r/min and 150 mm/min is noticed.…”
Section: Welding Force Characteristicsmentioning
confidence: 99%
“…Conversely, a special scroll feature on shoulder with a passage to extract material in form of self-detachable flash is designed that subsequently avoids imperfections, such as the step or sticky surface toe flash, observed in case of FSC with shoulder-workpiece clearance and FSC with tilt angle and toe flash. [9,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] The extracted material is collected in the form of self-detachable flash that can be reused with a separate processing technique, e.g. Friction Extrusion Process.…”
Section: Friction Stir Channeling Without Shoulderworkpiece Clearancementioning
confidence: 99%
“…Variations in vertical force acting on tool's probe during channel formation phase for position control mode and force control mode. [56] increased stress concentration on probe (that acts as cantilever beam without shoulder's support). For example, Pandya et al [67] reported that the tool's probe is failed during channel processing phase when subjected with shoulder-workpiece clearance.…”
Section: Forces and Torque During Processingmentioning
confidence: 99%
See 1 more Smart Citation